1995
DOI: 10.1002/dev.420280304
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rearing condition on activity‐induced weight loss

Abstract: This study evaluated the effects of differential rearing conditions on a rat protocol for various human syndromes. Subjects were 26 male Sprague-Dawley rats, 24 days old at the start of the experiment, matched according to weight, and randomly assigned to an isolation- or group-reared (4 rats/cage) condition. At 60 days of age (273 +/- 13 g), subjects were individually housed in cages allowing access to running wheels. Weight loss was produced through voluntary exercise and restricted food access. Animals in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…These results are in agreement with previous studies, which reported similar changes in female Sprague-Dawley rats (Hermes et al, 2011;Ness et al, 1995). Although we have not found changes in body weight in adulthood induced by the perinatal MK-801 injection, treated rats showed less weight when weighed at P21.…”
Section: Discussionsupporting
confidence: 95%
“…These results are in agreement with previous studies, which reported similar changes in female Sprague-Dawley rats (Hermes et al, 2011;Ness et al, 1995). Although we have not found changes in body weight in adulthood induced by the perinatal MK-801 injection, treated rats showed less weight when weighed at P21.…”
Section: Discussionsupporting
confidence: 95%
“…The standard ABA procedure, whereby rats live continuously in the equipment, ensures such isolation. When rats were given only limited access to a wheel each day and were otherwise housed either in group or individual cages, weight loss was more pronounced in the individually housed rats (Boakes & Dwyer, 1997; see also Ness, Marshall, & Aravich, 1995; Paré, Vincent, & Natelson, 1985). This suggests that the weight loss generated by the standard ABA procedure is accentuated by the isolation the procedure imposes.…”
Section: Methodsmentioning
confidence: 99%
“…After 6 weeks of social isolation started at PND21, neither thymus nor body weights were affected [36]. Five-week social isolation in Sprague Dawley rats starting at PND24 decreased body weights and increased thymus weights in the rats [39]. Cruz et al [103] found a reduction in male Wistar rats' body weights after 3 weeks of social isolation started at PND28.…”
Section: Serum Corticosterone Concentrations and Thymus Spleen And Adrenal Weightsmentioning
confidence: 99%
“…Adrenal glands (the adrenal cortex) secrete CORT into the blood and regulate basal and functional hormonal levels [101]. The changes in their relative weight in socially isolated rats are sex-dependent: In male rats, there were no differences in adrenal gland weights (after 5, 6, and 8 weeks of social isolation in Wistar and Sprague Dawley rat lines) [36][37][38][39][40], while in females, the weights of the adrenal glands increased (13 and 14 weeks of social isolation in hooded and Wistar rats) [35,37]. Our results are in good agreement with these data.…”
Section: Serum Corticosterone Concentrations and Thymus Spleen And Adrenal Weightsmentioning
confidence: 99%